A Year Without a Winter. - Hannah, Dehlia; Buckell, Tobias; Cooper, Brenda; D'Arcy Wood, Gillen; Eschrich, Joey; Graham, James; Hartnett, Hilairy; Higgins, David; Kress, Nancy; Lord, Byron; Okorafor, Nnedi; Selin, Cynthia; et al. (New York : Colombia University, 2018)
Charrière, Julian ; Sobecka, Karolina
Klimaatsverandering, Tambora, Mary Shelley, utopische architectuur, Paolo Soleri, Antartica, Frankenstein, Subawa, sciencefiction
boek
Keywords: Hannah, Dehlia